Sleep behaviors and metabolic-associated fatty liver disease - Yuqing Cai; Jia Chen; Xiaoyu Deng; Caiyun Wang; Jiefeng Huang; Ningfang Lian (PLoS ONE, 2025)
Objective This study aimed to comprehensively evaluate the association between various sleep behaviors and the risk of metabolic-associated fatty liver disease (MAFLD), particularly self-reported snoring. Methods Multivariate logistic regression was used to explore independent factors associated with MAFLD. ROC curve and decision curve analyses were used to analyze and compare the different indicators. Results A total of 3708 patients were enrolled, and 41.4% of them had MAFLD. According per multivariate logistic regression analysis, self-reported snoring was an independent predictor of MAFLD (p < 0.001), particularly the occasional and frequent snoring groups [OR (95% CI): 1.44 (1.12–1.87), 1.48 (1.15–1.91), p < 0.001]. In addition, the liver function levels and incidence rates of metabolic parameters were independently associated with the severity of self-reported snoring (all p < 0.05). Subgroup analyses suggested that the frequency of snoring was independently related to the risk of MAFLD in young and middle-aged patients (both p < 0.05), and was no longer associated with any frequency of self-reported snoring in the subgroup older than 60 years (p = 0.400). In both female and male subgroup, subjects who snored frequently had a higher odds risk of MAFLD than those who did not (both p < 0.05). The area under the ROC curve for snoring was 0.638, which was superior to that of the other indicators for MAFLD prediction (all p < 0.001). Meanwhile, decision curve analysis showed that snoring had a better clinical net benefit compared to other biomarkers, with a threshold probability (Pt) of approximately 0.3–0.6. Conclusion Self-reported snoring was an independent risk factor for MAFLD in young and middle-aged subjects with a moderate predictive value. Therefore, intense monitoring and evaluation of MAFLD in these patients is necessary.